2016
DOI: 10.1111/1752-1688.12461
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Trends in Nutrient and Sediment Loading to Lake Tahoe, California‐Nevada, USA

Abstract: Since 1980, the Lake Tahoe Interagency Monitoring Program (LTIMP) has provided stream‐discharge and water quality data—nitrogen (N), phosphorus (P), and suspended sediment—at more than 20 stations in Lake Tahoe Basin streams. To characterize the temporal and spatial patterns in nutrient and sediment loading to the lake, and improve the usefulness of the program and the existing database, we have (1) identified and corrected for sources of bias in the water quality database; (2) generated synthetic datasets for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Field observations support the presence of cyanobacteria in Lake Meredith and Grapevine Lake ( Trevino and Petersen, 2020 ). Lake Tahoe, a highly studied ultra- oligotrophic lake in California known for its water clarity (e.g., Beutel and Horne, 2018 ; Coats et al, 2016 ), had no detectable cyanobacteria in any resolvable weekly composites across the lake as demonstrated through an average annual lake-scale bloom frequency of 0%.…”
Section: Resultsmentioning
confidence: 99%
“…Field observations support the presence of cyanobacteria in Lake Meredith and Grapevine Lake ( Trevino and Petersen, 2020 ). Lake Tahoe, a highly studied ultra- oligotrophic lake in California known for its water clarity (e.g., Beutel and Horne, 2018 ; Coats et al, 2016 ), had no detectable cyanobacteria in any resolvable weekly composites across the lake as demonstrated through an average annual lake-scale bloom frequency of 0%.…”
Section: Resultsmentioning
confidence: 99%
“…The Blackwood watershed has https://www.ecologyandsociety.org/vol27/iss2/art6/ a long history of soil erosion caused by both natural characteristics and anthropogenic disturbances (historical excessive grazing, road construction, forest harvest) and has been the target of several stream channel restoration projects (Oehrli 2013, Norman et al 2014. Other studies, including those used to develop a total maximum daily load program, also identified Blackwood Creek and Ward Creek as the greatest sources of sediment and phosphorus pollutants in the Lake Tahoe basin (Tetra Tech 2007, Coats et al 2016, along with Upper Truckee River and Trout Creek watersheds on the south side of the basin, which are outside the study area that we examined.…”
Section: Strategies For Treating Highly Erodible Areasmentioning
confidence: 98%
“…The model runs are also archived in the HydroShare repository and contain both the input and the output data from the model, among other useful information. The watershed names reflect the watershed names used in other studies, which provided the observed water quality data for model assessment [3] . The streamflow for Mica Creek watersheds, MC3 and MC6, were recorded with flumes.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Modeled streamflow was compared to data from the USGS gauging stations for watersheds in the Lake Tahoe basin, Bull Run, and Cedar River watersheds, and data measured with flumes in the Mica Creek Experimental Watersheds, Idaho. Modeled sediment and phosphorus yield was compared to flow-weighted annual observations processed by [3] . Figs.…”
Section: Data Descriptionmentioning
confidence: 99%